Safe operation and maintenance of dry dock facilities - Harren, Paul A. (American Society of Civil Engineers, 2010)
Prepared by the Dry Dock Asset Management Task Committee of the Ports and Harbors Committee of the Coasts, Oceans, Ports, and Rivers Institute of ASCE Safe Operation and Maintenance of Dry Dock Facilities is the first manual of practice to provide guidance for the operation of four main types of dry dock facilities: floating dry docks, graving docks, marine railways, and vertical lifts. Until now, some of these facilities have been operated and maintained without a thorough understanding of the design of their dry docks and, therefore the features that are vital to the safe operation of the facility. This manual provides a cost-effective program for maintaining and operating a safe dry dock facility by examining in depth condition assessment, maintenance, control inspection, and dock operations. This manual is an essential safety and management references for engineers and managers working for commercial entities that operate dry docks.
Keywords: Dry docks -- Maintenance and repair.; Dry docks -- Safety measures.; elektronické knihy; electronic books